Multisensory integration of olfaction - Österbauer, R; Robert Alexander sterbauer (2007)
﻿ The primary aim of this thesis was to investigate, using functional magnetic resonance imaging (fMRI), the neurophysiological basis of multisensory integration involving smell and vision. To achieve this goal, several technical challenges had to be addressed: the attainment of sufficiently high quality fMRI images in olfactory brain regions within the orbitofrontal cortex (OFC), the construction of a stimulus delivery system adequate for rapid and controlled odour delivery in the MRI environment, and optimal strategies for delivering and perceiving liquid flavour stimuli in the scanner. In two initial fMRI experiments, strategies including sensitivity encoding and passive shimming to improve OFC image quality were explored. The results demonstrated that both methods can improve signal detection in OFC, a brain area particularly sensitive to susceptibility artefacts. In a further fMRI study, the effectiveness of two methods of delivering odorants dissolved in liquids was compared. In this study, the same set of participants was required to either swallow the liquid immediately after delivery or hold it in their mouths for a brief period of time. The results indicated that while both methods allowed detection of activity in primary olfactory and gustatory cortices, activation of the OFC was not observed when participants swallowed the liquids immediately. This was presumed to be due to the increased head motion associated with swallowing. Finally, the mechanisms underlying visual-olfactory integration were investigated using a combination of behavioural and imaging methods. An initial behavioural study revealed strong colour-odour associations for certain smells associated with fruits (e.g. lemon - yellow). In a subsequent fMRI study, volunteers were presented with a selection of the most colour-associated odours from the prior behavioural study either in isolation or in the presence of congruent and incongruent colours. Analysis of the fMRI data revealed that a highly left lateralised network of brain areas comprising of the OFC and insular showed increasingly stronger responses to odour-colour combinations of higher congruency. In a follow-up fMRI study, this same network was also found to be responsible for integrating odours, not only with colours, but also with their corresponding visual images (objects). In sum, the series of fMRI studies undertaken in this thesis argue for a fundamental role of the OFC in the integration of olfactory-visual inputs in the human brain.